Implementasi Budaya Keselamatan Pasien oleh Perawat di Rumah Sakit Ibnu Sina Makassar - Syam, Nur Syarianingsih (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2017)
Background: The incidence of medication errors to patients on hospital have been reported in some cases. Indonesia was launched "Patient Safety Movement in Hospital" to reduce incidence of medication errors. This movement was launched on 2005 ago, but until now its implementation has not been comprehensive. Method: This research used quantitative descriptive design using questionnaire as a measuring tool. This research could provide an overview of the implementation of patient safety culture in Ibnu Sina Hospital Makassar. Service that is. The data were processed by using univariate analysis with SPSS program. Results: The results of this study showed a positive response on the position of supervisor/manager expectations and patient safety promotion actions (82.3%) and the negative response was non-punitive response dimension (51.8%). The highest positive response was the inpatient installation (43.26%). Conclusion: The conclusion of this research is the impelentation of patient safety culture at the hospital of Ibnu Sina Makassar showed a positive response.